Emotional Labor Meanings, Gender, and Culture: A Comparative Assessment. Issue 4 (2nd October 2018) - Guy, Mary E.; Azhar, Aisha
Abstract : Thinking globally, acting locally. Regardless of nation, much of the work of public administration occurs at the street level and involves emotional labor. This article queries the linguistics of emotive expression for public service workers around the globe and in the process, explores nuances of gender. Of interest are these questions: Does emotive expression get lost in translation between the sexes? Are there gendered linguistic nuances to emotional labor that mask meanings? What is the influence of national culture? To answer, we compare the degree to which women and men respond similarly to questions about how they perform the emotive aspects of their jobs. Results show that culture and gender intertwine to shape how women and men interpret words. There is more commonality between women's and men's meanings in those cultures at the extremes of masculinity and femininity. At the center, where the masculinity/femininity of the culture is more ambiguous, the meanings of men and women are most diverse.